PES : PROGRAM E-BOOKING SALON BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Muhamad Ikbal Septiana; Fransisco Fransisco; Arroyan Ilham Nafian; Muhammad Rizal Ahmad; Hilda Rachmi (Pusat Riset dan Inovasi Nasional, 2024)
In the modern era, the evolution of the beauty industry, particularly beauty salons, has become a significant part of the demand for personal appearance and preferences. This article discusses the importance of implementing a Web-Based E-Booking System for salons, offering a solution to customers facing relatively long waiting times for salon services. This system aids in providing clear information regarding salon operating hours, price lists, and effectively manages queue numbers when customers visit. Through the application of fundamental website development concepts using technologies like HTML, CSS, PHP, and MySQL, this system enables customers to book services online. Thus, it explores the design, business process analysis, system architecture, and interface ensuring convenience, comfort, and efficiency for both salons and customers.